Analisa Usability pada Website Disdukcapil Kabupaten Ketapang - Sari, Novita Dayang; Ratmananda, Diasta; Zulfikar, M Rizki; Putri, Risky Setiani; Natasia, Sri R (Jurnal Kridatama Sains dan Teknologi, 2023)
The importance of website-based e-SIAK at the Ketapang Regency Population and Civil Registry Service as a public information medium that can provide information effectively and efficiently. This research aims to evaluate the level of usability of the Ketapang Regency Dukcapil website, identify existing usability problems, and provide recommendations for improvements to improve user experience. The method used in this research is usability testing involving a group of participants from the community who frequently use population services. Data obtained from usability testing is analyzed using qualitative and quantitative techniques to identify problems faced by users when interacting with the website. The results of this analysis are then used as a basis for developing recommendations for improvements that can increase the level of user satisfaction and efficiency in using the Ketapang Regency Disdukcapil website. The research results showed that, (1) The Usability Testing method, which involves user participation in system testing, has proven to be an effective approach for evaluating the usability and performance of a website or application. (2) The use of the System Usability Scale (SUS) in this research provides a consistent and tested way to measure user satisfaction with the system being tested. (3) This research shows that although Usability Testing methods provide valuable insights, there remain several challenges in optimizing system usability.Keywords: Usability Testing, Usability, Disdukcapil